Arabidopsis TAC Position Viewer: a high‐resolution map of transformation‐competent artificial chromosome (TAC) clones aligned with the Arabidopsis thaliana Columbia‐0 genome - Hirose, Yoshitsugu; Suda, Kunihiro; Liu, Yao-Guang; Sato, Shusei; Nakamura, Yukino; Yokoyama, Koji; Yamamoto, Naoki; Hanano, Shigeru; Takita, Eiji; Sakurai, Nozomu; Suzuki, Hideyuki; Nakamura, Yasukazu; et al. (Wiley, 2015)
We present a high‐resolution map of genomic transformation‐competent artificial chromosome (TAC) clones extending over allArabidopsis thaliana(Arabidopsis) chromosomes. The Arabidopsis genomicTACclones have been valuable genetic tools. Previously, we constructed an Arabidopsis genomicTAClibrary consisting of more than 10 000TACclones harboring large genomicDNAfragments extending over the whole Arabidopsis genome. Here, we determined 13 577 end sequences from 6987 ArabidopsisTACclones and mapped 5937TACclones to precise locations, covering approximately 90% of the Arabidopsis chromosomes. We present the large‐scale data set ofTACclones with high‐resolution mapping information as a Java application tool, the ArabidopsisTACPosition Viewer, which provides ready‐to‐go transformable genomicDNAclones corresponding to certain loci on Arabidopsis chromosomes. TheTACclone resources will accelerate genomicDNAcloning, positional walking, complementation of mutants andDNAtransformation for heterologous gene expression.